2023
DOI: 10.1002/adfm.202311920
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Breakthrough of Cell Membrane Barrier for Transmembrane Substance Exchange: A Review of Recent Progress

Liying Wang,
Xinyu Zhu,
Chengyan Xu
et al.

Abstract: Cell membrane composed of lipid bilayer is a selectively permeable membrane that only allows specific molecules to pass through. While such selectivity is essential for the survival and function of cells, there exist instances when it is necessary to overcome the cell membrane barrier. Study on the artificial cell membrane barrier breakthrough strategies is of great significance for the development of drug delivery systems and the understanding of cellular behaviors. Herein, the advancements in the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 178 publications
0
1
0
Order By: Relevance
“…This suggests that future investigations should not rely on pH-triggered release for successful transfection. Small size, dynamic membrane properties, and intracellular environment pose challenges in transfecting T cells [ 121 ]. To address these challanges, Ramishetti et al, formulated targeted LNPs by incorporating various designs whereby these LNPs showed specificity by targeting only primary T cells instead of nonimmune cells.…”
Section: Barriers To Overcome In Lnps-mediated Deliverymentioning
confidence: 99%
“…This suggests that future investigations should not rely on pH-triggered release for successful transfection. Small size, dynamic membrane properties, and intracellular environment pose challenges in transfecting T cells [ 121 ]. To address these challanges, Ramishetti et al, formulated targeted LNPs by incorporating various designs whereby these LNPs showed specificity by targeting only primary T cells instead of nonimmune cells.…”
Section: Barriers To Overcome In Lnps-mediated Deliverymentioning
confidence: 99%